2013
DOI: 10.1615/jlongtermeffmedimplants.2013007073
|View full text |Cite
|
Sign up to set email alerts
|

MiR146a and MiR499 Gene Polymorphisms in Iranian Periodontitis and Peri-implantitis Patients

Abstract: MiR146a (rs2910146) and MiR499 (rs3746444) gene polymorphisms may be genetic determinants for increased risk of chronic periodontitis and peri-implantitis in Iranians. More studies with larger sample sizes in different populations are necessary for determining the effect of these SNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
1
21
2
Order By: Relevance
“…However, although peri-implant infections are well described histopathologically, the molecular events that govern the development of these infections have not yet been completely characterized. Certain studies have attempted to correlate miRNAs with the pathogenesis of peri-implantitis [ 26 ]. In particular, it has been noted that miR-146a and miR-499 gene polymorphisms may be genetic determinants of an increased risk of peri-implantitis in Iranians.…”
Section: Discussionmentioning
confidence: 99%
“…However, although peri-implant infections are well described histopathologically, the molecular events that govern the development of these infections have not yet been completely characterized. Certain studies have attempted to correlate miRNAs with the pathogenesis of peri-implantitis [ 26 ]. In particular, it has been noted that miR-146a and miR-499 gene polymorphisms may be genetic determinants of an increased risk of peri-implantitis in Iranians.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an association of miRNA146a gene polymorphism with periodontitis in southIndian and Iranian population. 18,19 This microRNA146a is in turn regulated by the apolipoprotein E. ApoE regulates inflammation by suppressing the NF-kβ signaling. ApoE increases the expression of the transcription factor PU.1 and which in turn increases miRNA146a levels to suppress the NF-kβ signaling.…”
Section: Hypothesesmentioning
confidence: 99%
“…A study conducted comparing gingival (gum) biopsy samples derived from chronic periodontitis subjects, peri-implantitis (dental implants) subjects, and healthy subjects showed significant differential expression of miR-146a and miR-499 among these groups. 83 Various studies comparing healthy versus diseased gingiva have demonstrated specific miRNA deregulations in periodontal tissue homeostasis and pathology targeting TLR and TNF-α pathways. 10,11,84 Furthermore, our pilot investigation sought to determine whether miRNA expression differed in gingival biopsies obtained from obese/non-obese subjects with or without periodontal disease.…”
Section: Periodontal and Endodontic Diseasesmentioning
confidence: 99%